Maternal high-fat diet-induced microbiota changes are associated with alterations in embryonic brain metabolites and adolescent behaviour - Ratsika, Anna (2024)
The developing central nervous system is highly sensitive to nutrient changes during the perinatal period, emphasising the potential impact of alterations of maternal diet on offspring brain development and behaviour. A growing body of research implicates the gut microbiota in neurodevelopment and behaviour. Maternal overweight and obesity during the perinatal period has been linked to changes in neurodevelopment, plasticity and affective disorders in the offspring, with implications for microbial signals from the maternal gut. Here we investigate the impact of maternal high-fat diet (mHFD)-induced changes in microbial signals on offspring brain development, and neuroimmune signals, and the enduring effects on behaviour into adolescence. We first demonstrate that maternal caecal microbiota composition at term pregnancy (embryonic day 18: E18) differs significantly in response to maternal diet. Moreover, mHFD resulted in the upregulation of microbial genes in the maternal intestinal tissue linked to alterations in quinolinic acid synthesis and elevated kynurenine levels in the maternal plasma, both neuronal plasticity mediators related to glutamate metabolism. Metabolomics of mHFD embryonic brains at E18 also detected molecules linked to glutamate-glutamine cycle, including glutamic acid, glutathione disulphide, and kynurenine. During adolescence, the mHFD offspring exhibited increased locomotor activity and anxiety-like behaviour in a sex-dependent manner, along with upregulation of glutamate-related genes compared to controls. Overall, our results demonstrate that maternal exposure to high-fat diet results in microbiota changes, behavioural imprinting, altered brain metabolism, and glutamate signalling during critical developmental windows during the perinatal period.